2014
DOI: 10.1007/s10439-014-1183-5
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Chondrocytes in High-Stiffness Agarose Microenvironments for In Vitro Modeling of Osteoarthritis Mechanotransduction

Abstract: In articular cartilage, chondrocytes reside within a gel-like pericellular matrix (PCM). This matrix provides a mechanical link through which joint loads are transmitted to chondrocytes. The stiffness of the PCM decreases in the most common degenerative joint disease, osteoarthritis. To develop a system for modeling the stiffness of both the healthy and osteoarthritic PCM, we determined the concentration-stiffness relationships for agarose. We extended these results to encapsulate chondrocytes in agarose of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…For example, the PCM can release FGF2, a fibroblast growth factor, to initiate diverse signaling in response to external stimuli [25]. This study used previously published data involving SW1353 chondrocytes subjected to compression in agarose of physiological stiffness [10, 14]. SW1353 cells were selected because they are a commonly used in chondrocyte and osteoarthritis research [2628].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the PCM can release FGF2, a fibroblast growth factor, to initiate diverse signaling in response to external stimuli [25]. This study used previously published data involving SW1353 chondrocytes subjected to compression in agarose of physiological stiffness [10, 14]. SW1353 cells were selected because they are a commonly used in chondrocyte and osteoarthritis research [2628].…”
Section: Methodsmentioning
confidence: 99%
“…daily activity [9], have the potential to alter the energy metabolism of chondrocytes via mechanotransduction. We have previously observed changes in concentrations of central energy metabolites as a result of dynamic compression [10]. Other studies demonstrate that chondrocytes sense compression and can distinguish between static compression, dynamic compression, and even shear.…”
Section: Introductionmentioning
confidence: 99%
“…cellular metabolites smaller than ∼1000 Da). Building upon previous methodology to encapsulate chondrocytes in agarose similar in stiffness to the human PCM, we profiled the metabolomic responses of primary human OA chondrocytes in response to applied compression at physiological levels [20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…While healthy cartilage has PCM stiffness values of ~40kPa, the stiffness of osteoarthritic PCM is ~24kPa (Alexopoulos et al, 2005). Current studies have analyzed 3D cultures in 1–3% (v/v) agarose hydrogels, which has a stiffness ranging from 15–19kPa (Jutila et al, 2015), falling to the lower boundary for OA PCM environments and providing limited data on the progression of chondrocyte mechanotransduction pathways from healthy to OA. However, recent advances have characterized mechanical properties of higher concentration agarose hydrogels and found that the stiffness of 4.5% (v/v) agarose hydrogels approaches that of healthy PCM.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances have characterized mechanical properties of higher concentration agarose hydrogels and found that the stiffness of 4.5% (v/v) agarose hydrogels approaches that of healthy PCM. Therefore, comparing 2 and 4.5% agarose hydrogels provide an opportunity for studying altered mechanotransduction in OA disease progression (Jutila et al, 2015). …”
Section: Introductionmentioning
confidence: 99%